Problem reprezentacji w teoriach poznania ucieleśnionego - Natika Newton (Avant, 2012)
This paper looks at a central issue with embodiment theories in cognition: the role, if any, they provide for mental representation. Thelen and Smith (1994) hold that the concept of representations is either vacuous or misapplied in such systems. Others maintain a place for representations (e.g. Clark 1996), but are imprecise about their nature and role. It is difficult to understand what those could be if representations are understood in the same sense as that used by computationalists: fixed or long-lasting neural structures that represent the sensory stimuli that caused them (e.g. neural response patterns in the visual cortex), or whose “meaning” is fixed innately or in early development for particular functions (e.g. the body schemas for Meltzoff and Gopnik 1993). The paper proposes a distinctions between, on the one hand, neural patterns, traces of sensory activation that while not in themselves representations are available for representational activity, and on the other the act of representing, which is what gives representational content to neural patterns.